Child Labor Trafficking in the United States: A Hidden Crime - Kaufka Walts, Katherine (2017)
Emerging research brings more attention to labor trafficking in the United States. However, very few efforts have been made to better understand or respond to labor trafficking of minors. Cases of children forced to work as domestic servants, in factories, restaurants, peddling candy or other goods, or on farms may not automatically elicit suspicion from an outside observer as compared to a child providing sexual services for money. In contrast to sex trafficking, labor trafficking is often tied to formal economies and industries, which often makes it more difficult to distinguish from "legitimate" work, including among adolescents. This article seeks to provide examples of documented cases of child labor trafficking in the United States, and to provide an overview of systemic gaps in law, policy, data collection, research, and practice. These areas are currently overwhelmingly focused on sex trafficking, which undermines the policy intentions of the Trafficking Victims Protection Act (2000), the seminal statute criminalizing sex and labor trafficking in the United States, its subsequent reauthorizations, and international laws and protocols addressing human trafficking.